Diabetes, child care, and performance of family functions - Ewa Kobos; Jacek Imiela; Anna Leńczuk-Gruba (Studia Medyczne, 2017)
Introduction : Parents caring for a child with diabetes may experience a burden on both a practical and an emotional level. Aim of the research : Analysis of the correlations between the care burden level and the perceived influence of type 1 diabetes in children on the performance of family functions. Material and methods : The study included 112 caregivers of children with diabetes. The following inclusion criteria were taken into account: full family, direct caregiver of the child, the child’s age 3–16 years, disease duration of at least 6 months, and no chronic diseases in siblings. The study material was collected using an interview questionnaire and the Caregiver Burden Scale. Correlation analysis was performed using the Spearman correlation coefficient. The significance level was defined as p = 0.05. Results : A higher burden level of a caregiver in the individual subscales of the CB Scale was associated with a significant decrease in the intensity of performance of the cultural and social function as well as consumption function, the increased amount of time spent with a sick child, and an increase in parental disagreements. The overall burden level differentiated the performance of the religious function. An increase in the burden level on the overall effort subscale was accompanied by lower interest in sex and less frequent sexual intercourse. The higher level of caregiver burden occurs in families where permanent job income has fallen. The differences were shown in the performance of control-socialisation function due to the sense of burden on the environment subscale. Conclusions : The burden level of a caregiver is important in the perceived influence of the child’s illness on the functioning of the family. Stimulating a caregiver in dealing with the problems that are the consequence of the disease, as well as activating and preparing other family members to participate in the care of a sick child, and financial support may reduce the caregiver burden and thus facilitate the functioning of the family.